Leitura de textos em língua inglesa: construindo uma prática dialógica de leitura - Quartezan, Vagner (2010)
This thesis aimed at developing the critical-reflective standpoint of the teacher with a view to improving the teaching-learning of English, especially in terms of reading. The investigation presented here is based on the concepts of reading as social practice (Bloome, 1983), on the socio-cultural-historical perspective of teaching-learning (Vygotsky 1984/2000), on theories of reading processes and their relationship with the concept of literacy (Kleiman, 1995), and on the practice of thinking aloud in group (Zanotto, 1995/1998). The methodology employed for this research is embedded in the qualitative approach of action-research (Kincheloe, 1993), and data generation (Mason, 1996) took place by audio-recording the group think-aloud experiences. In order to analyze the data, the categories used were those of mediation by the teacher (Vygotsky, 1984/2000), as well as orchestrating and re-voicing (O Connor & Michaels, 1996). Results obtained from the data analysis reveal that the teacher plays the role of mediator and facilitator in the reading activity, supporting students so that they can become more autonomous. The research has also showed that students make use of both cognitive and metacognitive strategies, which are adapted to the individual learning styles